Cisco LAN switching fundamentals: the essential guide for understanding ethernet switched network - Barnes, David; Sakandar, Basir (Indianapolis, IN : Cisco Press, 2005)
It presents an in-depth look at modern campus network requirements, It provides an easy to understand introduction to LAN switching best practices using Cisco Catalyst Switches. It also provides a wealth of details on the architecture, operaton, and configuration of the Cisco Catalyst family of switches.
Includes index.
uaj 2/12/2013
Loans
Keywords: Telecommunication; Local area networks (Computer networks)